Comparação de métodos de plantio de Pinus spp. - F Barros, Nairam; B Vale, Antônio; M Brandi, Renato; L Collom, James (Revista Ceres, 2025)
Survival and initial growth of three types of seedlings, with and without application of triple super phospate, were studied in Viçosa, Minas Gerais, Brasil, using Pinus oocarpa cubensis (Mexico), P. oocarpa (Honduras), P. insularis (Burma), P. cubensis (Costa Rica) and P. pseudostrobus var. oaxacana (Mexico).